IMPLEMENTASI MANAJEMEN STRATEGIS KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MASA PANDEMI COVID-19 (SEBUAH STUDI KASUS PEMBELAJARAN DARING DI SDK PENABUR KOTA MODERN KOTA TANGERANG) [IMPLEMENTATION OF PRINCIPALS' STRATEGIC MANAGEMENT IN IMPROVING TEACHER PERFORMANCE DURING THE COVID-19 PANDEMIC (A CASE STUDY OF ONLINE LEARNING AT SDK PENABUR KOTA MODERN, TANGERANG] - Murwanto, Marthynus Agung; Hardiman, Fransisco Budi (Universitas Pelita Harapan, 2024)
AbstractThe COVID-19 pandemic has impacted all aspects of life. The impact can be categorized as a crisis. Changes that occurred in the education sector as a result of this crisis changed the system and patterns of learning. Learning in the era of the COVID-19 pandemic is carried out by distance learning or online. This study aims to obtain information about the principal's managerial strategy in improving teacher performance, especially in dealing with changes in the way of learning that occur, the implementation and evaluation of the principal's managerial strategy in online learning activities in times of crisis. This research uses a qualitative approach with a case study method. For data collection, researchers used interviews, document studies and observation. The results of the study are 4 principal management which includes: planning, implementation, supervision, organization and the seven principles carried out by school principals in dealing with changes in the implementation of learning in schools due to the crisis, including: 1) calm, 2) confident, 3) communication, 4) cooperation, 5) community, 6) concern, 7) financial ability in dealing with crises at school. By implementing the management strategy of the principal, the teacher's performance can be improved. The approach taken by the principal in overcoming the crisis can help improve performance so that services to students and parents can be provided to the maximum. Bahasa Indonesia AbstrakPandemi Covid-19 berdampak pada semua aspek kehidupan. Dampak yang ditimbulkan dapat dikategorikan dengan krisis. Perubahan yang terjadi pada ranah pendidikan akibat krisis ini mengubah sistem dan pola pembelajaran. Pembelajaran pada era pandemi Covid-19 dilakukan dengan pembelajaran jarak jauh atau online. Penelitian ini bertujuan untuk memperoleh informasi tentang manajemen strategi Kepala Sekolah dalam meningkatkan kinerja guru khususnya dalam menghadapi perubahan cara pembelajaran yang terjadi, implementasi serta evaluasi manajemen strategi Kepala Sekolah pada kegiatan pembelajaran daring di masa krisis. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Untuk pengumpulan data peneliti menggunakan wawancara, studi dokumen dan observasi. Hasil penelitian yaitu 4 manajemen Kepala Sekolah yang meliputi: perencanaan, pelaksanaan, pengawasan, pengorganisasian serta tujuh prinsip yang dilakukan kepala sekolah dalam menghadapi perubahan pelaksanaan pembelajaran di sekolah akibat krisis yang terjadi antara lain: 1) tenang, 2) percaya diri, 3) komunikasi, 4) kerjasama, 5) komunitas, 6) kepedulian, 7) kemampuan finansial dalam menghadapi krisis di sekolahan. Dengan menjalankan strategi manajemen dari Kepala Sekolah akhirnya kinerja guru dapat ditingkatkan. Pendekatan yang dilakukan Kepala Sekolah dalam mengatasi krisis dapat membantu meningkatkan kinerja sehingga pelayanan terhadap peserta didik dan orang tua dapat diberikan dengan maksimal.